USULAN TINDAKAN PREVENTIVE MAINTENANCE DAN PERAMALAN PERMINTAAN DALAM RANGKA MEMAKSIMALKAN LABA BERDASARKAN METODE LINEAR PROGRAMMING PADA DEPARTEMEN INJECTION PT OMNI KEMAS INDUSTRY - Nurhasanah, Nunung; Felix, Felix; Wilson, Wilson; Eka, Christina (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
The Injection Department of PT Omni Kemas Industry has several problems in machinesâÂ breakdown and in forecasting the customersâ demand. Besides that, the company also wants to maximizeÂ their profit. Therefore, the aim of this final assignment is to minimize the machinesâ breakdown, demandÂ forecasting and profit maximizing. This final assignment counts the frequencies and intervals of preventiveÂ replacements and inspections based on preventive maintenance method and also forecasts customersâÂ demand based on the smallest error generated by the methods. Then, the outputs from the preventiveÂ maintenance and demand forecasting are used in production amount optimalizing process in order to gainÂ profit maximizing.